Grit as a moderator: the mediating role of self-efficacy and academic performance between conscientiousness and life satisfaction among college students - Li, Jianan; Ma, Tingting; Lee, Chang Seek (Frontiers in Psychology, 2025)
IntroductionIn recent decades, academic research has established the significant influence of personality traits on life satisfaction. However, the mediating and moderating mechanisms underlying the relationship between conscientiousness and life satisfaction remain insufficiently understood, warranting further investigation.MethodsThis study aimed to clarify the moderated mediation mechanism linking conscientiousness, academic self-efficacy, academic performance, grit, and life satisfaction. To this end, an exploratory hypothetical model was proposed, and empirical verification of the model was conducted via a random sampling survey. The respondents of this study were 304 undergraduate and professional students from China. The data analysis tools used in this study included SPSS AMOS Version.26, SPSS Statistics Ver.25 and SPSS PROCESS Macro-Ver.4.2.ResultsThe results showed that conscientiousness, academic self-efficacy, academic performance, life satisfaction and grit were positively correlated. Grit played a moderating role in the dual mediating relationship from conscientiousness to academic self-efficacy to academic performance to life satisfaction.DiscussionThe research results provided new ideas for explaining the formation mechanism of college students’ life satisfaction, and provided more targeted suggestions on using grit to intervene and improve students’ happiness in school.